The Radio/X-Ray Correlation in X-Ray Binaries-Insights from a Hard X-Ray Perspective - Karri I. I. Koljonen; David M. Russell (IOP PUBLISHING LTD, 2022)
The radio/X-ray correlation is one of the most important pieces of observational evidence of the disk-jet connection in accreting compact objects. However, a growing number of X-ray binaries (XRB) seem to present deviations from the universal radio/X-ray correlation, and the origin of these outliers are still very much debated. In previous studies, the X-ray bolometric luminosity used in the radio/X-ray correlation has been estimated using a narrow, soft X-ray band. We study how estimating the X-ray bolometric luminosity using broadband observations of XRB affects the radio/X-ray correlation. We found that the ratio between the broadband (3-200 keV) and narrowband (3-9 keV) luminosities varies between 5 and 10 in the hard X-ray state. Overall, the resulting radio/X-ray correlation slopes and normalizations did not present a very significant change, suggesting that they are not affected greatly by observational biases but are caused by real physical effects. We found that all sources that reach high enough luminosity change their correlation slopes from the universal slope to a much steeper one. In addition, sources in the steeper radio/X-ray track show a distinct cutoff in the high-energy X-ray spectrum at tens of keV. These results suggest that the accretion flow presents a morphological change at a certain critical luminosity during the outburst rise from radiatively inefficient to radiatively efficient flow that is in turn more efficient in cooling the hot accretion flow producing the hard X-ray emission. This change could also affect to the jet launching properties in these systems.